Computer organization and design : the hardware/software interface - Patterson, David A. (The Morgan Kaufmann series in computer architecture and design, 2012)
"Presents the fundamentals of hardware technologies, assembly language, computer arithmetic, pipelining, memory hierarchies and I/O"--